P136 Questions clinicians are asked when offering patients pleurodesis: a survey of practice. (11th November 2022) - Sundaralingam, A; Addala, D; Bedawi, E; Denniston, P; Iqbal, B; Hallifax, R; Kanellakis, N; Wrightson, J; Rahman, N
Abstract : Introduction: Patients with malignant pleural effusions (MPE) have few options available to them for definitive effusion control. Options include an indwelling pleural catheter or pleurodesis. Both are described as palliative interventions with no impact on disease course. Unsurprisingly patients often enquire whether a pleurodesis leaves them at risk of the redirection of malignant fluid elsewhere. This survey sought to understand how often clinicians are faced with such queries from patients and how they respond to these valid concerns. Methods: An online survey was distributed to Lung Cancer Nursing UK, Mesothelioma UK, UK Pleural Society members and Respiratory trainee networks. Results: The survey received a total of 87 respondents. 38/87 (44%) were consultant respiratory physicians, 20% were cancer nurse specialists, 25% were trainee respiratory physicians and 11% were pleural nurse specialists. Phrases clinicians used to describe the mechanism of action for pleurodesis are shown in figure 1 . 64% of respondents indicated that they had been asked by patients if fluid is redirected. 24/73 (33%) reported this happened in at least half of their consultations. Clinician responses to these concerns varied, but the most common response was 'No, this doesn't happen, nothing to worry about, ' (20/63, 32%), followed by 'Yes, this might happen, but we can deal with it…' (22%) and 'We don't know' (16%). 75% of respondents were not aware of any evidence to support these reassurances. The remaining 25% provided their own clinical experience and their understanding of the mechanisms of MPE formation and of pleurodesis as the basis for reassurance. There were no statistically significant associations between how pleurodesis is explained to patients, clinician role or being asked about fluid re-direction. Discussion: Redirection of malignant fluid appears to be a commonly held concern by patients when offered pleurodesis. Many clinicians provide reassurances to patients that this is unlikely to occur but accept there is a paucity of evidence to support these reassurances. These data may have exposed a gap in our understanding of the mechanisms underpinning pleurodesis and warrant consideration in future MPE research.